Tissue Damage, Not Infection, Triggers Hepatic Unfolded Protein Response in an Experimental Rat Peritonitis Model - Müllebner, Andrea; Herminghaus, Anna; Miller, Ingrid; Kames, Martina; Luís, Andreia; Picker, Olaf; Bauer, Inge; Kozlov, Andrey V.; Duvigneau, Johanna Catharina (Frontiers in Medicine, 2022)
Background: Abdominal surgery is an efficient treatment of intra-abdominal sepsis. Surgical trauma and peritoneal infection lead to the activation of multiple pathological pathways. Liver is particularly susceptible to injury under septic conditions. Liver function is impaired when pathological conditions induce endoplasmic reticulum (ER) stress. ER stress triggers the unfolded protein response (UPR), aiming at restoring ER homeostasis, or inducing cell death. In order to translate basic knowledge on ER function into the clinical setting, we aimed at dissecting the effect of surgery and peritoneal infection on progression of ER stress/UPR and inflammatory markers in the liver in a clinically relevant experimental animal model. Methods: Wistar rats underwent laparotomy followed by colon ascendens stent peritonitis (CASP) or surgery (sham). Liver damage (AST, ALT, de Ritis values), inflammatory and UPR markers were assessed in livers at 24 h, 48 h, 72 h and 96 h post-surgery. Levels of inflammatory (IL-6, TNF-, iNOS and HO-1), UPR (XBP1, GRP78, CHOP) and apoptosis (BAX/Bcl-XL) mRNA were determined by qPCR. Splicing of XBP1 was analyzed by gel electrophoresis, p-eIF2 and GRP78 protein levels using western blots. Results: AST levels were elevated 24 h after surgery and thereafter declined with different kinetics in sham and CASP groups. Compared to sham De Ritis ratios were significantly higher in the CASP group, at 48 h and 96 h. CASP induced an inflammatory response after 48 h, evidenced by elevated levels of IL 6, TNF , iNOS, and HO 1. In contrast, UPR markers, XBP1s, p eIF2, GRP78, XBP1 and CHOP did not increase in response to infection, but paralleled the kinetics of AST and De Ritis ratios. We found that inflammatory markers were predominately associated with CASP, while UPR markers were associated with surgery. However, in the CASP group we found a stronger correlation between XBP1s, XBP1 and GRP78, and damage markers, suggesting a synergistic influence of inflammation on UPR in our model. Conclusion: Our results indicate that independent mechanisms induce UPR and inflammatory responses in the liver. While peritoneal infection predominantly triggers inflammatory responses, conditions associated with organ damage are predominant triggers of the hepatic UPR.